Continuous versus intermittent administration of ceftazidime in experimental Klebsiella pneumoniae pneumonia in normal and leukopenic rats. - Roosendaal, R (1986)
Experimental Klebsiella pneumoniae pneumonia was used to study the influence of cyclophosphamide-induced leukopenia on the relative therapeutic efficacy of continuous and intermittent (6-h intervals) administration of ceftazidime. The antimicrobial response was evaluated with respect to the calculated daily dose that protected 50% of the animals from death (PD50) until 16 days after the termination of a 4-day treatment. When ceftazidime was administered intermittently to leukopenic rats, the PD50 was 24.37 mg/kg per day, 70 times (P less than 0.001) the PD50 of 0.35 mg/kg per day for normal rats. Continuous administration of ceftazidime to leukopenic rats resulted in a PD50 of 1.52 mg/kg per day, four times (P less than 0.001) the PD50 of 0.36 mg/kg per day for normal rats. Continuous administration of ceftazidime in daily doses that protected 100% of normal and leukopenic rats from death resulted in serum levels of 0.06 and 0.38 micrograms/ml, respectively, whereas the MIC for the infecting K. pneumoniae strain was 0.2 micrograms of ceftazidime per ml. The effect of the duration of ceftazidime treatment by continuous infusion on the therapeutic efficacy in relation to the persistence of leukopenia was then investigated in leukopenic rats. The administration of 3.75 mg of ceftazidime/kg per day for 4 days protected all leukopenic rats from death, provided the circulating leukocytes returned at the end of antibiotic treatment. When leukopenia persisted for 8 days this ceftazidime treatment schedule resulted in the mortality of rats (P less than 0.05). However, when ceftazidime treatment was continued for 8 days, until the return of the leukocytes, there was no significant mortality (P greater than 0.05).